Food quality : balancing health and disease - Holban, Alina Maria; Grumezescu, Alexandru Mihai; ScienceDirect eBooks (London : Academic Press, an imprint of Elsevier, 2018)
Food Quality: Balancing Health and Disease, Volume Thirteen in the Handbook of Food Bioengineering series, provides essential information for researchers, scientists and students on the relationship between the quality of foods and disease at the biological level. It presents different technological approaches to detect food properties and their capabilities for balancing health and disease to deliver high-quality products to consumers. This volume explores the dynamic potential of how food bioengineering can improve traditional foods through modern methods to make a positive impact on human health and foster innovation.
Includes bibliographical references and index.
Vendor-supplied metadata.
Elsevier
Keywords: Food -- Quality; Food industry and trade -- Quality control; Nutrition; Bioengineering; TECHNOLOGY & ENGINEERING / Food Science; Bioengineering; Food industry and trade -- Quality control; Food -- Quality; Nutrition; Electronic books